Pengenalan Emosi Dasar dan Anti-Bullying sebagai Upaya Peningkatan Kesadaran Berempati dalam Masyarakat - Rachmawan Budiarto; Ridha Hanifah; Novi Astuti Indra Paranita; Rias Janathun Qolbi; Lintang Ratri Handaru Putri; Adrian Yoga Permana; Alvina Mita Iknawati; Alya Akmala Luthfiani Farras; Cahyo Indarti; Joko Sudibyo; Sujono (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
Bullying in the school environment is an emerging issue that needs to be taken care of by various parties. It will cause a negative impact on the future of both the perpetrator and the victim. Children may grow up with unstable emotions and have low empathy for others. The purpose of this activity is to introduce basic emotions and anti-bullying knowledge as an effort to increase empathetic awareness in the community in preventing bullying. Prospective comparative study with an observation and interview was carried out as the methodology, teachers, and parents. The research sample was selected using a purposive sampling method. Based on observations, it was found that there are behaviors that indicate bullying in the school environment. In addition, students were also found to have poor empathy and emotional management. The activity of introducing basic emotions and anti-bullying behavior utilized posters, mini games, and attaching stickers. This activity is targeted for grade 5 elementary school students because they are already able to recognize their emotions, and their experience will be an example for other students in another grade. Students, teachers, and parents who have been interviewed stated that this emotional recognition and anti-bullying activity was excellent and had a positive impact on children's emotional development. Students increasingly understand the meaning of basic emotions and anti-bullying, recognize self-emotions, know how to express emotions, increase empathy, and create a more comfortable school environment.